2022
DOI: 10.1007/s10342-022-01473-5
|View full text |Cite
|
Sign up to set email alerts
|

Age-independent diameter increment models for mixed mountain forests

Abstract: Mixed mountain forests with an uneven-aged structure are characterized by a high tree-growth variability making traditional age-dependent growth models inapplicable. Estimating site productivity is yet another impediment for modelling tree growth in such forests. Uneven-aged mixed-stand forests are known for their high resilience, resistance and productivity, and are being promoted as a suitable alternative to even-aged, pure plantations for climate change adaptation and mitigation. However, their growth must … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…A large number of studies report positive relationships between species diversity and forest productivity [122,263], and it has also been confirmed that diversity in forest species composition increases resistance to biotic insect pest calamities [261,264]. Therefore, declining forest stands in Central Europe are often replaced by mixtures of tree species in an attempt to adapt forests to climate change [255,262,265,266]. Much of the Central European forest landscape is still dominated by Norway spruce, despite its documented susceptibility to drought, wind, bark beetles, etc.…”
Section: Impact Of Climate Changementioning
confidence: 97%
“…A large number of studies report positive relationships between species diversity and forest productivity [122,263], and it has also been confirmed that diversity in forest species composition increases resistance to biotic insect pest calamities [261,264]. Therefore, declining forest stands in Central Europe are often replaced by mixtures of tree species in an attempt to adapt forests to climate change [255,262,265,266]. Much of the Central European forest landscape is still dominated by Norway spruce, despite its documented susceptibility to drought, wind, bark beetles, etc.…”
Section: Impact Of Climate Changementioning
confidence: 97%